2009
DOI: 10.1002/chem.200802472
|View full text |Cite
|
Sign up to set email alerts
|

Thermally Stable Solids Based on Endohedrally Doped ZnS Clusters

Abstract: The existence of inorganic, hollow, fullerene-like ZnS clusters has been theoretically predicted and then recently confirmed experimentally. These clusters were observed to trap alkali metals and halogens because the ionization energies (IE) of alkali metals are very similar to the electron affinities (EA) of halogens. This opens the possibility of forming molecular solids composed of these fullerene building blocks because the energy released due to the difference between the IE and EA would be very small. He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 51 publications
2
18
1
Order By: Relevance
“…In this work, our calculated optimum lattice parameter is found to be 13.25 Å with a distance of 2.546 Å between monomers. It is obvious that the lattice parameter we obtained is a little smaller than that of Matxain et al 62 The differences in lattice parameters may be attributed to bond lengths of the intermonomer Zn-S bonds. We found that each monomer in the structure 12-3 has two types of Zn-S bonds, a longer one (2.458 Å) in four-membered rings and the other shorter one (2.378 Å) connecting the neighboring fourmembered rings, which are larger than those of isolated monomers.…”
Section: Systemcontrasting
confidence: 79%
See 1 more Smart Citation
“…In this work, our calculated optimum lattice parameter is found to be 13.25 Å with a distance of 2.546 Å between monomers. It is obvious that the lattice parameter we obtained is a little smaller than that of Matxain et al 62 The differences in lattice parameters may be attributed to bond lengths of the intermonomer Zn-S bonds. We found that each monomer in the structure 12-3 has two types of Zn-S bonds, a longer one (2.458 Å) in four-membered rings and the other shorter one (2.378 Å) connecting the neighboring fourmembered rings, which are larger than those of isolated monomers.…”
Section: Systemcontrasting
confidence: 79%
“…This structural framework was also investigated by Matxain et al in a study on thermally stable solids based on endohedrally doped ZnS clusters. 62 Since the centers of Zn 12 S 12 cages favor the bulk fcc structure, they predicted that the structure of the characterized solid has a cubic unit cell with lattice parameters of Fig. 5 The optimized stable structures of frameworks assembled by Zn 16 S 16 clusters.…”
Section: Structural and Electronic Properties Of Cluster-assembled Ma...mentioning
confidence: 99%
“…Therefore, assemblies of small clusters would lead to AF materials, while assemblies of large clusters would lead to F materials, being the AF coupling close in energy. Moreover, considering the Ag-Ag distances in these dimers, along with related studies on other encapsulated X@ZnS and X@CdS assemblies [44,45], we suggest that the Ag-Ag distances would remain quite similar in the solid compared to the dimers.…”
Section: Dimersupporting
confidence: 61%
“…The stability of ZnS nanostructures has also been reported by several other experimental and simulation studies. In [46], the stability of endohedrally doped ZnS clusters has been confirmed by ab initio simulations. In [47], a wet‐chemical precipitation method is optimised for the synthesis of ZnS nanocrystals doped with Cu+ and halogen.…”
Section: Resultsmentioning
confidence: 95%